Imunoterapia no cancro do pulmão: PD-L1, biomarcador preditivo? - Carolina Jorge Oliveira Gonçalves (2020)
Lung cancer remains one of the types of oncological disease that leads to greater morbimortality. Immunotherapy is one of the most recent advances relatively the therapeutic options available. As numerous clinical trials have been showing, this targeted therapy allows to increase the likelihood of achieving more favorable clinical results, particularly in some patients with advanced non-small cell lung carcinomas - the most prevalent type. It is urgent to gather scientific evidence on what determinants will be associated with clinical results, in order to promote an optimized and judicious resource to immunotherapy. One of the complex mechanisms that this therapy explores is the molecular interactions of the PD-1/PD-L1 pathway, and thus, predictably due to its pathophysiological role, the expression of the PD-L1 ligand has been evaluated as a potential predictive biomarker, being currently the only predictive factor approved by competent entities to be considered in concrete situations. Reflecting on this plausible ability to select patients using the PD-L1 assessment is the objective of this review. Despite divergent conclusions in the literature, globally, an association between the level of expression of PD-L1 and clinical results is recognized. Multiple grounds for the discrepancy, occasionally verified, regarding its relevance as a potential biomarker will be listed. In parallel, different hypothetical targets for potential predictive tools, ideally combined, are being investigated. It can be concluded that the PD-L1, the first established predictive biomarker and of undoubted relevance, in isolation remains insufficient to be applied as the unique criterion of election/exclusion for the use of immunological checkpoint inhibitors (ICI) and on which it will be important, therefore, to further study.